Prioritization of Occupational Accident Causes in the Automotive Manufacturing - Syed, M. Z.; Khalique, A.; Idrees, M. D.; Jamil, A.; Sami, A.; Abdullah, A.; Sajid, N.; Khan, K.; Rizvi, S. (Engineering, Technology & Applied Science Research, 2022)
The automotive industry is a significant contributor to the economy. Additionally, it is prone to occupational accidents. The current study focuses on organizational accidents in high-risk activities, particularly occupational accidents in the automobile and manufacturing industries. This investigation aims to rank and quantify the causes of occupational accidents. These reasons are identified through a literature review and are investigated utilizing the Analytical Hierarchy Process (AHP). An AHP model is built based on a literature review. This model created a questionnaire and its evaluation via a survey of experts’ opinions. This study shows that the most significant and dominant elements in accidents are human and organizational factors since they receive roughly equal weighting, whereas environmental factors weigh less.